1995
DOI: 10.1002/pd.1970150813
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound diagnosis of the pena shokeir phenotype at 14 weeks of pregnancy

Abstract: This report describes the early prenatal diagnosis of the Pena Shokeir phenotype in an at-risk patient at 14 weeks' gestation. The diagnosis was based on an abnormal fetal movement profile, in association with an abnormal position of the fetal limbs. Pena Shokeir phenotype describes an inherited condition characterized by arthrogryposis and dysmorphic features as a result of fetal akinesia. It is a lethal abnormality and early diagnosis allows safer surgical methods of termination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 11 publications
(7 reference statements)
0
27
0
2
Order By: Relevance
“…In case of the absence of specific movement patterns beyond the age of 10 wk, PMA pathologic development should be strongly suspected. This has been shown for spontaneous abortion (7), anencephaly (9), and fetal akinesia deformation sequence (10,11). In addition, we hypothesize that the absence of variable and complex movements beyond 10 wk indicates the presence of supraspinal dysfunction caused, for instance, by a genetic disorder or an early insult to the brain.…”
Section: Fetal Onset Of General Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of the absence of specific movement patterns beyond the age of 10 wk, PMA pathologic development should be strongly suspected. This has been shown for spontaneous abortion (7), anencephaly (9), and fetal akinesia deformation sequence (10,11). In addition, we hypothesize that the absence of variable and complex movements beyond 10 wk indicates the presence of supraspinal dysfunction caused, for instance, by a genetic disorder or an early insult to the brain.…”
Section: Fetal Onset Of General Movementsmentioning
confidence: 99%
“…Some case reports suggested that neural dysfunction in the first trimester of pregnancy may induce changes in the differentiation and the qualitative and quantitative performance of specific movement patterns. For example, deviances in motor development during the first trimester have been reported for acquired disorders such as spontaneous abortion (7) or exposure to maternal type 1 diabetes (8) and in fetuses with congenital anomalies such as anencephaly (9) and fetal akinesia deformation sequence (10,11). However, how the various movement patterns develop from their first appearance onward has not been fully investigated.…”
mentioning
confidence: 99%
“…Sepulveda et al [15] reported on the prenatal diagnosis of another case at 19 weeks, the pregnancy was terminated and the fetus had generalised skin oedema, bilateral pleural effusions and severe flexion contracture deformities. Ajayi et al [16] also reported an early prenatal diagnosis in an atrisk patient at 14 weeks of gestation. The diagnosis was based on an abnormal fetal movement profile in association with an abnormal position of the fetal limbs.…”
Section: Discussionmentioning
confidence: 97%
“…Bu vakada da üst ve alt ekstremiteler simetrik ve bilateral olarak etkilenmişti. Ancak vakada pulmoner hipoplazi yoktu [7]. Pena-Shokeir fenotipik olarak trizomi 18'e benzediği için ayırıcı tanısının yapılması gerekir.…”
Section: Discussionunclassified